Traffic detectors deployment modeling and optimization under urban road network - Hanjie Ye; Jianming Hu; Xudong Xie; Yi Zhang (2016 12th World Congress on Intelligent Control and Automation (WCICA), 2016)
Due to the poor development of economy and policy, small and medium-sized city road networks, compared with large cities, are lack of management about traffic infrastructures and data, which causes a large amount of problems. Thus, building perfect detecting networks is necessary in these small and medium-sized cities to help regulate the traffic. However, models built in present researches about detectors deployment are too simple to be applied in a real environment. Therefore, in this paper, different models will be made based on different objective functions. Besides, much more situations of the road network and detectors are considered to build models. To solve these complex discrete models, an optimization algorithm is proposed. Other than common discrete optimization algorithm, Fruit Fly Optimization Algorithm (FOA) is introduced in this paper and applied for discrete optimization. A part of the road network of Haining, a typical medium-sized city, is the experiment subject to proof our method.